Diseño y comparación de una estructura de acero vs. una estructura de aluminio para una cubierta de 19.5 m de luz y 6 m de ancho a una altura de 12.3 m con dos apoyos posteriores. - Paredes Terán, César Antonio (2014)
The purpose of this thesis is a comparative analysis of two structures, similarly with different materials, steel and aluminum, in order to obtain the most viable economic option and structural strength. In the first capítulose based on a comprehensive theoretical analysis of the appropriate use of structural materials, advantages and disadvantages of both types of structures in steel and aluminum, clamps, gaskets, bearings, allowable stress, load types acting focusing on methods calculation for the structural analysis and design. In the second chapter the calculation and design of the steel structure is determined, the initial parameters are the data on the location and general characteristics for design.